2016
DOI: 10.11604/pamj.2016.24.238.8535
|View full text |Cite
|
Sign up to set email alerts
|

Proximal-type epithelioid sarcoma: a new case report and literature review

Abstract: Proximal-type epithelioid sarcoma is a rare soft tissue neoplasm which arises from the more proximal part of body and occurs more often in young people; the definite diagnosis depends mainly on the pathological examination; early detection and complete excision remain the foundation of treatment. Due to its aggressive behavior, high capacity of recurrence and the great ability to metastasize, a careful clinical long-term monitoring is required. We report a new case of a 20 years old girl, presented with proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Histopathology and immunohistochemistry studies confirmed the diagnosis. Surgical resection was the only treatment, and the patient did not develop any recurrence of the lesion at 18 months of follow-up [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology and immunohistochemistry studies confirmed the diagnosis. Surgical resection was the only treatment, and the patient did not develop any recurrence of the lesion at 18 months of follow-up [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A greater rate of survival has also been shown to be associated with the more common of the two histological ES subtypes: the distal-type [20]. Distal ES is often seen in the extremities while proximal ES typically affects the trunk, axilla, and groin among other proximal sites [21]. Debate on whether the proximal-type is inherently worse than distal ES or whether it is due to their associations with the affected site persists [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Proximal-type ESs are extremely rare and are notorious for high local recurrence rates and distant metastasis in up to 60% of cases (17,18). These tumors, when arising in proximal locations, have a very poor prognosis than those arising in distal locations.…”
Section: Discussionmentioning
confidence: 99%